Analisis Sikap Disiplin melalui Penerapan Metode Pembiasaan pada Anak Usia 4-5 Tahun di PAUD Putri Tahun Ajaran 2018/2019 - Sondang Purba; Niken Farida; Suliah Suliah (Journal on Education, 2023)
The research is aimed to analyze the increase in the development of the attitude of the discipline through the method of habituation in children aged early 4-5 in group A in PAUD PUTRI academic year of 2018/2019. Subject of this research is a children's group A in kindergarten which totally 20 children. As for the type of research this is the kind of research descriptive based time sampling. The study was conducted in the second semester of the 2018/2019 school year . Techniques of collecting data used in this research is the observation and the results show of the work attitude of the discipline of children in group A. The instrument of collecting the data using a sheet of observation and pieces of work of children . Analysis of the data used is qualitative and quantitative descriptive analysis . The development of PUTRI In academic year of 2018/2019. Based on the analysis of data the attitude of discipline through the application of methods of habituation in children 4-5 years on aspects of the child came on right time are 16 childrens or 80% in the category Emerging Very Good (BSH) and 4 childrens , or 20% are in category start growing (MB ). On average attitude of discipline through the application of methods of habituation in children 4-5 years on aspects of children were able to comply with the rules of the time in a play that is 16 childrens or 80% in the category Emerging Very Good (BSH) and 4 children or 20% are in category start developing (MB).